The association between human development and citizen happiness in Indonesia: Study at 34 Provinces of Indonesia - Hanafi, Imam; Salsabilla, Sekar Aqila (Gema Wiralodra, 2024)
Work on happiness and human development share a common lineage, both have been driven partly by an interest in understanding and measuring human progress and well-being. The paradox of the relationship between human development and happiness encourages us to examine the factors that influence happiness. The study of happiness is considered to be important in public administration due to public administration's concern with the relationship between government and society. For policies and programs to be truly effective to this end, they must gain a better understanding of happiness. This research uses a quantitative approach as the research design with the correlational study. This study uses two units of analysis, the first one being provinces in Indonesia and the second one being people. The Provincial data used are taken from the Central Bureau of Statistics (Badan Pusat Statistik) (BPS), about 34 Provinces. The second level unit is individuals or people and uses data from Survey Pengukuran Tingkat Kebahagian (SPTK) 2017 conducted by the Central Bureau of Statistics (BPS), which consists of 72,317 household heads. The result shows that human development is associated with citizen happiness in Indonesia. Overall, HDI is associated with happiness. These findings suggest that improving human development is fundamental for the happiness of Indonesian citizens, especially improving expected years of schooling, mean years of schooling, and income per capita.